Effect of mixing procedure and steam curing on the properties of Class C fly ash-cement based Geopolymer - Romy Suryaningrat Edwin; Sulha Sulha; Fitriah Masud; Wayan Mustika (SINERGI, 2024)
This work investigated the performance of class C fly ash-cement- based geopolymer paste with different mixing procedures and under steam curing. The geopolymer paste containing class C fly ash was mixed with cement up to 20% at 10% increments. The alkaline activator was prepared 24 hours before mixing by blending Na2SiO3 and NaOH 14 M with a ratio of 2:1. Two methods of mixing procedure were used in this study to mix the geopolymer pastes. Steam curing at 90 ± 5 °C for six hours was applied. Setting time, compressive strength and strength activity index were used in this research for performance analysis. According to the results, the setting time of geopolymer paste containing 100% C type flash ash is delayed by the use of method 2 in the mixing process. While, adding cement content speeds up both the initial and final setting times of fresh geopolymer pastes. Additional water at the early stage in the mixing process (method 2) generated excellent polymerization at longer curing periods. In contrast, the potentially agglomeration of fly ash and cement in the polymer matrix was observed after applying method 1, which is the reason for the lower strength of geopolymer paste. The strength activity index (SAI) of geopolymer paste containing cement increased at early curing periods for all mixing methods. The early-stage benefits of steam curing are achieved in geopolymer pastes containing 0% cement when mixed using techniques 1 and 2.